(untitled) (REMUNOM, 2025)
Leptospirosis is an acute febrile disease, particularly prevalent in developing tropical countries worldwide. It manifests in both urban and rural environments, with distinct characteristics related to occupational or recreational activities. The most commonly affected age group comprises young and young adult individuals. Approximately 5% to 15% of patients develop the severe form of the disease, which may be associated with organic complications. This report describes a case of a patient admitted to a University Hospital in Western Paraná, Cascavel-PR. The patient experienced a fulminant and atyical progression of the disease with 18 days of evolution, being monitored from 02/15/2023 to 03/04/2023.